Keanekaragaman Jenis Burung Air Dalam Upaya Konservasi Keanekaragaman Hayati di Kawasan Pesisir Pantai Timur Kabupaten Labuhanbatu Utara - Putra, Chairunas Adha; Hikmatullah, Desy; Rambe, Raja Banggas; Siregar, Mahdalenawaty; Pradana, Tengku Gilang; Muammar (Sagita Academia Journal, 2025)
The eastern coast of North Sumatra supports one of the province’s remaining mangrove ecosystems, which provide critical ecological functions and serve as key habitats for resident and migratory waterbirds along the East Asian–Australasian Flyway (EAAF). This study surveyed the coastal wetlands of Labuhanbatu Utara Regency including mangrove forests, mudflats, and aquaculture ponds to document species composition, population size, and the conservation significance of the area. Fieldwork was conducted at multiple sites in Kualuh Leidong and Kualuh Hilir between 6–8 December 2024, complemented by earlier surveys from 2019 and 2020. Using concentration counts and block estimation methods during rising to high tide conditions, we recorded 36 waterbird species, consisting of 17 resident and 19 migratory species, with total counts of 4,602 individuals (2019), 7,695 individuals (2020), and 2,368 individuals (2024). Twelve species are legally protected in Indonesia, including Ardea alba, Mycteria cinerea, and Leptoptilos javanicus. Globally threatened species were also documented, such as the Endangered Milky Stork (Mycteria cinerea) and three Vulnerable species including the Chinese Egret (Egretta eulophotes). Several migratory shorebirds exceeded the 1% population threshold of the EAAF, notably the Tibetan Sand Plover (Anarhynchus atrifrons, 1.2%), Whimbrel (Numenius phaeopus, 1.4%), Eurasian Curlew (N. arquata, 1.1%), and Common Redshank (Tringa totanus, 1.2–1.3%). These findings confirm that the coastal wetlands of Labuhanbatu Utara constitute an internationally important site for migratory waterbirds, highlighting the urgent need for strengthened conservation and habitat protection in the region.